SWOT Analysis of BBK Electronics' Product Diversification Strategy for Dominating Indonesia's Smartphone Market - Mashudan, Muhammad Vajri; Maesaroh, Sity Sarah; Nugraha, Muhammad Rizki (Dinasti Publisher, 2025)
Marketing strategy encompasses planning, pricing, promotion, and distribution to meet consumer needs. This study analyzes BBK Electronics' product diversification strategy in capturing Indonesia's smartphone market using SWOT analysis. The findings indicate that BBK Electronics is positioned in Quadrant I, demonstrating strong capabilities to capitalize on opportunities despite intense competition. The company can enhance competitiveness by improving product quality, expanding its service network, and optimizing brand positioning.